2020
DOI: 10.1016/j.omtn.2020.08.039
|View full text |Cite
|
Sign up to set email alerts
|

circFN1 Mediates Sorafenib Resistance of Hepatocellular Carcinoma Cells by Sponging miR-1205 and Regulating E2F1 Expression

Abstract: In recent years, circular RNAs (circRNAs) have been shown to have critical regulatory roles in the resistance to anti-cancer drugs. However, the contributions of circRNAs to sorafenib resistance in hepatocellular carcinoma (HCC) remain largely unknown. The present study aims to explore the involvement of circFN1 in sorafenib resistance and how circFN1 is associated with the miR-1205/E2F1 pathway, which have been demonstrated to mediate this resistance in HCC cells. We investigated the expression of circRNAs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…A large number of studies performed on HCC patients have shown that hsa_circ_0000798 [174] hsa_circ_0027089 [175] and hsa_circ_0058124 [176] are upregulated in HCC tissues, whereas some circRNAs are downregulated, including hsa_circSMARCA5 [177] hsa_circ_0068669 [178] hsa_circ_0028502 [179] and hsa_circ_0076251 [179] . These circRNAs are supposed to serve as potential biomarkers for HCC.…”
Section: Circrnas Are Promising Biomarkers In Cancermentioning
confidence: 99%
“…A large number of studies performed on HCC patients have shown that hsa_circ_0000798 [174] hsa_circ_0027089 [175] and hsa_circ_0058124 [176] are upregulated in HCC tissues, whereas some circRNAs are downregulated, including hsa_circSMARCA5 [177] hsa_circ_0068669 [178] hsa_circ_0028502 [179] and hsa_circ_0076251 [179] . These circRNAs are supposed to serve as potential biomarkers for HCC.…”
Section: Circrnas Are Promising Biomarkers In Cancermentioning
confidence: 99%
“…Therefore circRNA_101237 was an independent predictor of prognosis in HCC patients 102 . circFN1 (hsa_circ_0058124) was found to be able to promote the expression of E2F1 by acting as a miR-1205 sponge; thus, inhibition of circFN1 could enhance the sensitivity of HCC cells to sorafenib 103 . circARNT2 (hsa_circ_0104670) regulated cisplatin resistance through the miR-155-5p/PDK1 axis, while downregulation of circARNT2 inhibited cell proliferation and enhanced the sensitivity of HCC cells to cisplatin 104 .…”
Section: The Roles Of Circrna In Hccmentioning
confidence: 99%
“…Our group has made continuous progress in this field and found that circSORE participates in the process of HCC sorafenib resistance [ 52 , 53 ]. Additionally, circFN1 was reported to induce HCC sorafenib resistance by sponging miR-1205 and modulating E2F1 expression [ 101 ].…”
Section: Role Of Circrnas In Hccmentioning
confidence: 99%